2011
DOI: 10.1371/journal.pone.0028348
|View full text |Cite
|
Sign up to set email alerts
|

Data and Image Transfer Using Mobile Phones to Strengthen Microscopy-Based Diagnostic Services in Low and Middle Income Country Laboratories

Abstract: BackgroundThe emerging market of mobile phone technology and its use in the health sector is rapidly expanding and connecting even the most remote areas of world. Distributing diagnostic images over the mobile network for knowledge sharing, feedback or quality control is a logical innovation.ObjectiveTo determine the feasibility of using mobile phones for capturing microscopy images and transferring these to a central database for assessment, feedback and educational purposes.MethodsA feasibility study was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 11 publications
1
61
0
Order By: Relevance
“…helminths or schistosomes) typically requires examination of significantly larger areas, especially with samples showing low levels of infection or when assessing infection rate. Benefits of digital microscopy compared to light microscopy include real-time data sharing for remote diagnosis and consultations to facilitate faster diagnosis [25,26], and the possibility of utilizing digital image analysis to aid in sample analysis [27]. …”
Section: Introductionmentioning
confidence: 99%
“…helminths or schistosomes) typically requires examination of significantly larger areas, especially with samples showing low levels of infection or when assessing infection rate. Benefits of digital microscopy compared to light microscopy include real-time data sharing for remote diagnosis and consultations to facilitate faster diagnosis [25,26], and the possibility of utilizing digital image analysis to aid in sample analysis [27]. …”
Section: Introductionmentioning
confidence: 99%
“…microscope; however, such a contraption is unsuitable to serve as a portable point-of-care test. 10 Although helminth eggs can reliably be visualized with our mobile phone microscope, it is often a challenge to appropriately speciate the infecting organism. In addition, the mobile phone microscope detected several false-positive eggs that were likely stool artifact because of the relative lack in image quality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the digitization of images may aid in diagnoses by enabling clinicians to transfer photos to centralized locations for diagnostic support. 10,19 Mobile phone diagnostic technology will likely contribute to the diagnosis of infections and non-infectious etiologies in resource-constrained settings. A first-generation mobile phone microscope using a ball lens had modest diagnostic yield for soil-transmitted helminth infections; however, newer technologies may further improve mobile phone diagnostic capabilities, but they require additional field testing in different epidemiologic settings.…”
Section: Discussionmentioning
confidence: 99%
“…Although broadband penetration is low in developing countries, remaining below 10 % in South Africa, smartphones have penetrated approximately 40 % of these areas [15,16]. Hence, based on information and communication technologies (ICT) infrastructure conditions in developing countries, portable smartphones are the best suited terminals for combinations of diagnostics and medical instruments, such as microscopes and electrocardiograms (ECG) [17,18]. Accordingly, smartphones have been used individually and with other components or devices to monitor cardiovascular disease [17].…”
Section: Smartphone-based Optical Systemsmentioning
confidence: 99%
“…Microscopic POC devices using smartphones were also developed during this decade. Specifically, Tujin et al conducted a feasibility study of microscopy-based diagnostic services to find microbes in body fluid using conventional staining techniques, such as Giemsa [18]. Moreover, Wei et al demonstrated the use of fluorescence microscopic diagnostic systems with smartphones to visualize single bacteria or viruses, and developed an immunostaining method and optical system using a cell phone attachment [19].…”
Section: Smartphone-based Optical Systemsmentioning
confidence: 99%